Virtual Air Temperature Function for Room Thermostats. (June 2019) - Nehasil, O; Horváthová, J; Kohoutková, A; Kny, M
Abstract: Room thermostats and indoor controllers are currently based on the air temperature set, which is a regulated quantity. The aim of the control is to keep the air temperature on its setpoint. The purpose is, however, to achieve and maintain thermal comfort in the indoor environment. Even so, thermal comfort is dependent on more parameters than simply air temperature. The thermal comfort function has been known since the 1970s, and has since been verified many times. This paper introduces a novel virtual air temperature function that can be used in indoor thermostats, that takes into account all important inputs for thermal comfort assessment, such as average radiant temperature and air velocity, as well as clothing, activity and user expectations. The method for obtaining listed input parameters is described and does not require more complex technical equipment than a conventional thermostat. In addition, the paper describes the actual function of the virtual air temperature that determines the comfort setpoint for the room thermostat. This function is verified in several operating states by both quantification and calculation. The results are compared against normal recommendations for determining the setpoint, and the difference in thermal comfort is discussed. Finally, the applicability of the equation to normal room thermostats is verified.